2012
DOI: 10.2337/dc11-1593
|View full text |Cite
|
Sign up to set email alerts
|

High Fat Intake Leads to Acute Postprandial Exposure to Circulating Endotoxin in Type 2 Diabetic Subjects

Abstract: OBJECTIVETo evaluate the changes in circulating endotoxin after a high–saturated fat meal to determine whether these effects depend on metabolic disease state.RESEARCH DESIGN AND METHODSSubjects (n = 54) were given a high-fat meal (75 g fat, 5 g carbohydrate, 6 g protein) after an overnight fast (nonobese control [NOC]: age 39.9 ± 11.8 years [mean ± SD], BMI 24.9 ± 3.2 kg/m2, n = 9; obese: age 43.8 ± 9.5 years, BMI 33.3 ± 2.5 kg/m2, n = 15; impaired glucose tolerance [IGT]: age 41.7 ± 11.3 years, BMI 32.0 ± 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
164
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(180 citation statements)
references
References 38 publications
9
164
1
6
Order By: Relevance
“…Bacterial LPSs derived from the outer membranes of Gram-negative bacteria have been intensively studied and are known to induce metabolic endotoxemia by promoting secretion of pro-inflammatory cytokines (17). Studies in both animal models and humans have shown that a high-fat diet can modulate the gut microbiota and increase circulating levels of LPSs, probably by uptake of LPSs in chylomicrons secreted from intestinal epithelial cells or through increased intestinal permeability (17,18,19,20). Mice fed a diet rich in fat exhibited increased adiposity and lowgrade inflammation dependent on LPS signalling, and infusion of LPSs in mice resulted in metabolic changes comparable to the high-fat feeding.…”
Section: Gut Microbiota and Host Metabolismmentioning
confidence: 99%
“…Bacterial LPSs derived from the outer membranes of Gram-negative bacteria have been intensively studied and are known to induce metabolic endotoxemia by promoting secretion of pro-inflammatory cytokines (17). Studies in both animal models and humans have shown that a high-fat diet can modulate the gut microbiota and increase circulating levels of LPSs, probably by uptake of LPSs in chylomicrons secreted from intestinal epithelial cells or through increased intestinal permeability (17,18,19,20). Mice fed a diet rich in fat exhibited increased adiposity and lowgrade inflammation dependent on LPS signalling, and infusion of LPSs in mice resulted in metabolic changes comparable to the high-fat feeding.…”
Section: Gut Microbiota and Host Metabolismmentioning
confidence: 99%
“…LPS is not only present locally in tissues such as periodontium when infection with gram-negative bacteria occurs; it also exists systematically in blood circulation at low concentrations (21). Interestingly, clinical studies have shown that circulating LPS is increased in patients with obesity (21,33), and animal studies have shown that TLR4 deficiency in mice protects against the development of insulin resistance (41).…”
mentioning
confidence: 99%
“…Interestingly, clinical studies have shown that circulating LPS is increased in patients with obesity (21,33), and animal studies have shown that TLR4 deficiency in mice protects against the development of insulin resistance (41). Taking these clinical and animal findings together, it is indicated that TLR4 signaling triggered by low concentrations of LPS may contribute to the inflammatory state that is essential for developing insulin resistance (50).…”
mentioning
confidence: 99%
“…Mixed hyperlipidic/hyperglucidic meals (51 g lipids, 81 g carbohydrates) also increase plasma LPS in the postprandial phase in healthy lean men (Ghanim et al, 2009. Recent studies confirm these results of postprandial endotoxemia in type 2 diabetic subjects consuming 75 g of lipids (Harte et al, 2012) and in morbidly obese subjects consuming a 50 g lipid load (Clemente-Postigo et al, 2012). Among postprandial studies, some used dairy fat (butter or cream), other used mixed fatrich foods (often eggs and sausage) or simple oil load or, in the form of single food or into mixed meals, and altogether fat intake was high (Tab.…”
Section: Intestinal Lipid Absorption Contributes To the Translocationmentioning
confidence: 77%